Higher magnesium depletion score increases the risk of all‑cause and cardiovascular mortality in US adults with diabetes - Hao Zhang; Liping Kuang; Qiang Wan (PLoS ONE, 2025)
Background Both dietary magnesium and serum magnesium are associated with the prognosis of diabetic patients. However, the impact of the magnesium depletion score (MDS), which assesses systemic magnesium deficiency, on the prognosis of diabetic patients remains unclear. This cohort study aims to explore the potential association between the MDS and all-cause and cardiovascular mortality in diabetic patients. Methods In this study, we analyzed data from 5,219 diabetic individuals from National Health and Nutrition Examination Survey (NHANES) 2003–2018. Participant mortality information was sourced from the National Death Index records. MDS was divided into lower MDS (0–1 points), middle MDS (2 points), and higher MDS (3–5 points) groups. Weighted multivariable Cox regression was utilized to explore the potential association between MDS and mortality in diabetic patients. Stratified analyses and sensitivity analyses were employed to validate the robustness of our findings. Results Among the 5,219 participants included in this study, 1,212 experienced all-cause mortality, and 348 experienced cardiovascular mortality. Weighted multivariable Cox regression indicated that higher MDS was strongly linked to a heightened risk of mortality in all models, including the fully adjusted model (all-cause mortality: HR = 1.58, 95% CI: 1.20–2.08; cardiovascular mortality: HR = 1.92, 95% CI: 1.28–2.88). In the stratified analysis, we found that the association between MDS and all-cause mortality was stronger among individuals aged <60 years. No significant differences were found in the relationship between MDS and mortality within other subgroups. In the sensitivity analyses, our results remained robust. Conclusions An increase in MDS is significantly correlated with a higher risk of all-cause and cardiovascular mortality in diabetic patients. The risk of all-cause mortality was higher in diabetic patients aged <60. Early monitoring and management of MDS, as well as optimizing magnesium nutritional status, may benefit diabetic patients.